Syntaxins 6 and 8 facilitate tau into secretory pathways. Issue 7 (16th April 2021) - Lee, Wei Siang; Tan, Daniel CS; Deng, Yuanyuan; van Hummel, Annika; Ippati, Stefania; Stevens, Claire; Carmona-Mora, Paulina; Ariawan, Daryl; Hou, Liming; Stefen, Holly; Tomanic, Tamara; Bi, Mian; et al.
Abstract : Tau pathology initiates in defined brain regions and is known to spread along neuronal connections as symptoms progress in Alzheimer's disease (AD) and other tauopathies. This spread requires the release of tau from donor cells, but the underlying molecular mechanisms remained unknown. Here, we established the interactome of the C-terminal tail region of tau and identified syntaxin 8 (STX8) as a mediator of tau release from cells. Similarly, we showed the syntaxin 6 (STX6), part of the same SNARE family as STX8 also facilitated tau release. STX6 was previously genetically linked to progressive supranuclear palsy (PSP), a tauopathy. Finally, we demonstrated that the transmembrane domain of STX6 is required and sufficient to mediate tau secretion. The differential role of STX6 and STX8 in alternative secretory pathways suggests the association of tau with different secretory processes. Taken together, both syntaxins, STX6 and STX8, may contribute to AD and PSP pathogenesis by mediating release of tau from cells and facilitating pathology spreading.